Bibliometric Analysis of Briquette Research Trends During the Covid-19 Pandemic - Al Husaeni, Dwi Novia (ASEAN Journal for Science and Engineering in Materials, 2022)
This study aims to analyze the scope of research on briquettes using bibliometric analysis and data mapping processes. The research data used is obtained from published journals. The search was conducted using the publish or perish application with the keyword "briquette'. The search process is based on topic areas with titles, keywords, and abstracts in the study material. The mapping process is carried out using VOSviewer. A total of 973 relevant articles were found. The results showed that research on briquettes has decreased over the past three years, namely 2020, 2021, and 2022. The decline was caused by the Covid-19 pandemic. Through VOSviewer we analyze the number of articles that have been published about the material and its relationship with the topic area. This review can certainly provide a reference point for further research related to the material.